De las causas próximas a las causas profundas del crecimiento económico de Bolivia entre 1950 y 2015 - Carlos Gustavo Machicado (Institute for Advanced Development Studies (INESAD), 2018)
– This paper analyzes Bolivia's long-term economic growth between 1950 and 2015, identifying its proximate causes through a growth accounting exercise, which considers the direct and indirect effects of Total Factor Productivity (TFP) on GDP per worker. The novelty is that the measurement of TFP that is obtained, takes into account the adjustment for quality and use of production factors (capital and labor). In addition, development accounting exercises are performed (in growth rates and levels) comparing the performance of the Bolivian economy with the Chilean economy, finding that although certain gaps have been closed with Chile, in recent years, it continues to be the low productivity the Achilles heel of the Bolivian economy. Finally, the fundamental causes of Bolivian economic growth are analyzed, with an emphasis on institutional, external, investment efficiency and financial factors. It is found that the terms of trade and macroeconomic stability are the fundamental determinants of TFP in Bolivia.
Keywords: E23; O11; O47; 330; Growth and development; Total Factor Productivity; Data